Physical activity domains are differently related with quality of life in breast cancer survivors: a cross-sectional study - Ribeiro, Fernanda E. [UNESP] (2021)
OBJECTIVES: Treatments for breast cancer (BC) can lead to physical and mental impairments which may affect quality of life (QoL). Physical activity (PA) is highly recommended for this population due to its protective effect against BC relapse and its ability to reduce the health impact of treatment. However, it is not clear whether the different domains of PA are associated with better QoL of BC survivors. The current study aimed to verify the relationship between different PA domains with QoL of BC survivors. METHODS: The sample consisted of 128 women BC survivors, with a mean age of 58.2 ± 9.7 years. QoL was assessed using the Short-Form Health Survey questionnaire (SF-36) and PA was verified through the Baecke questionnaire, in domains of occupation, sports practice, and leisure time/commuting. The relationship between QoL and different PA domains was verified by linear regression, adjusted by age, marital status, and socioeconomic condition. RESULTS: Occupational PA was negatively related to physical limitations [β= -15.36 (-29.04 to -1.68] and body pain [β=-6.61 (-14.53 to 1.31) marginal association]. Sports practice was positively related to functional capacity [β= 4.24 (0.60 to 7.88)]. Leisure time/commuting PA was positively related to functional capacity [β = 7.17 (3.09 to 11.26)], vitality [β = 4.30 (0.39 to 8.22)], social aspects [β= 5.47 (0.80 to 10.15)], and mental health [β = 4.08 (0.40 to 7.75)]. CONCLUSIONS: Sports practice and leisure time/commuting PA were positively related to QoL in BC survivors, while occupational PA was negatively related to QoL, independently of age, marital status, and socioeconomic condition.